Laju Urbanisasi dan Pertumbuhan Kota di Indonesia - Abdul Rahman (Universitas Negeri Makassar, 2023)
Abstract: Urbanization always give negative and positive influences to the development in any sectors. Impact that has been occurred from this process is not only be implicated to the aspect of spacing, but also to social, economy, and cultural aspect. The consequences of urbanization flow rapidly to urban area will cause the slum settlements spread widely, and the micro informal sectors are mushrooming. Informal sector is really developed rapidly and profitable, but it has a consequence to the increasing of poverty. This condition will disturb the urban structure because buffer area like